Educação inclusiva e as representações dos estudantes sobre seus pares com deficiência - Magnabosco, Molise De Bem; Souza, Leonardo Lemos De (Associação Brasileira de Psicologia Escolar e Educacional (ABRAPEE), 2018)
Abstract Inclusive education proposes the valuation of the diversity present in society, including people with disabilities. However, there is still a predominance of integrative practices in schools. The purpose of this research was to identify the representations that students without disabilities elaborate on the child with a physical disability in the daily school life. These representations had analyzed from the Theory of Thinking Models. Twenty-seven children aged 6 to 8 years participated in this study of schools in a municipal school network. They had interviewed individually, based on a fictitious situation of conflict. As results, we can list the prevalence of the medical model on the deficiencies, which unfold in prejudice and stigmatization. The representations had centered on the limitations of the subject with disability and the attribution, to him, of negative feelings. From this, there is a need to promote the understanding of inclusion based on a social perspective.

Resumen En la educación inclusiva se propone la valoración de la diversidad presente en la sociedad, incluso de las personas con deficiencia. Sin embargo, aún hay predominio de prácticas integradoras en las escuelas. El objetivo de esta investigación fue identificar las representaciones que los estudiantes sin deficiencia elaboran sobre el niño con deficiencia física en el cotidiano escolar. Se analizaron tales representaciones a partir de la Teoría de los Modelos Organizadores del Pensamiento. Participaron de este estudio 27 niños, de 6 a 8 años, de escuelas de una red municipal de enseñanza. Ellas fueron entrevistadas individualmente, con base en una situación ficticia de conflicto. Como resultados, podemos enumerar la prevalencia del modelo médico sobre las deficiencias, que se desdoblan en prejuicio y estigmatización. Las representaciones fueron centralizadas en las limitaciones del sujeto con deficiencia y en la atribución, a él, de sentimientos negativos. A partir de eso, se verifica la necesidad de la promoción de la comprensión de la inclusión fundamentada en una perspectiva social.

Resumo A educação inclusiva propõe a valorização da diversidade presente na sociedade, inclusive das pessoas com deficiência. Contudo, ainda há predomínio de práticas integradoras nas escolas. O objetivo desta pesquisa foi identificar as representações que os estudantes sem deficiência elaboram sobre a criança com deficiência física no cotidiano escolar. Tais representações foram analisadas a partir da Teoria dos Modelos Organizadores do Pensamento. Participaram deste estudo 27 crianças, de 6 a 8 anos, de escolas de uma rede municipal de ensino. Elas foram entrevistadas individualmente, com base em uma situação fictícia de conflito. Como resultados, podemos elencar a prevalência do modelo médico sobre as deficiências, que se desdobram em preconceito e estigmatização. As representações foram centralizadas nas limitações do sujeito com deficiência e na atribuição, a ele, de sentimentos negativos. A partir disso, verifica-se a necessidade da promoção da compreensão da inclusão fundamentada em uma perspectiva social.
Inclusive education and the representations of students on their patients with disabilities
Educación inclusiva y las representaciones de los estudiantes sobre sus pares con deficiencia
Keywords: Inclusive education; representation; prejudice; Educação Inclusiva; representação; preconceito